Students' Perception of Using Storytelling Technique to Improve Speaking Performance at SMPN 143 Jakarta Utara - Greta Natasia; Luh Angelianawati (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
Speaking is an essential skill to master in every foreign language learning. It even can be used to measure a foreign language learner’s success. However, learning to speak a foreign language, particularly English, is extremely difficult for beginners and to help them using storytelling is highly recommended (Haven, 2000; Caine, et al., 2005). However, learners’ perception is one of the most important success factors in any learning technique, including storytelling, because they are among the main stakeholders of learning. This study aims at exploring students’ perception of storytelling techniques use to improve speaking. Involving 74 students of SMPN 143 North Jakarta, the data was collected using a set of questionnaires. The results show that the participants had a positive perception of the use of storytelling techniques. They found the technique interesting, beneficial, and easy to use.